The clinical importance of the nasal valve - Gelardi, Matteo; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2019)
The nasal valve deserves relevant in patients presenting with nasal obstruction. In particular, the nasal valve plays an important role in nasal airflow control, it is relevant for the otolaryngologist to not only consider but also fully evaluate the nasal valve when seeing a patient with nasal obstruction. These data reported in this Supplement confirms the clinical relevance of the nasal valve in different groups of patients and normal subjects. In fact, an integrity of nasal valve is fundamental to ensure a physiological nasal breathing that in turn guarantees a correct pulmonary function. The possibility to use the non-surgical and well-accepted option constituted by the nasal internal dilator represent an interesting opportunity for both the physician and the patient.